The micro-politics of norm contestation between the OSCE and Kazakhstan: square pegs in round holes. Issue 9 (2nd September 2018) - Isaacs, Rico
Abstract: Norm contestation by local actors has emerged in recent years as an explanation for the failure of norm diffusion. This article contributes to the literature on norm contestation by analysing how norms diffused by the Organisation for Security and Cooperation in Europe (OSCE) pertaining to election observation and free and fair voting are re-constituted and contested by domestic actors in Kazakhstan. The study contributes to the idea of 'constitutive localisation' by emphasising a more fundamental level of disagreement beyond just congruence between the diffused norm and local beliefs; by demonstrating contestation can occur in the later stages in the norm diffusion cycle; by focusing on the micro-politics of contestation by local actors involved in the implementation of diffused norms; and by revealing how norm contestation is not necessarily a process of emancipatory politics, but a strategic act to serve authoritarian consolidation. Utilising a four-fold framework, the analysis illustrates how norms, while initially accepted by Kazakhstani authorities, are reconstituted through political discourse and/or practice, creating the moment of contestation . While this contestation is instrumentalised by political elites for their own advantage, it also remains an important element of agency within a normative order which they had little previous control over.